Аналіз балансу потужності вібраційних конвеєрів - Гаврильченко, Олександр (КІНПАТРІ ЛТД, 2013)
A statement of power of oscillation conveyer in composition of which the electromagnetic is included vibroexciter analysis is conducted, hesitating system, working organ, wares are transported, with the purpose of increase of his efficiency.
Statement of power of oscillation conveyers analysis